The thread-legged bugs (Hemiptera: Heteroptera: Reduviidae: Emesinae) of Lord Howe and Norfolk Islands - Tatarnic, Nikolai J.; Cassis, Gerasimos (Zootaxa, 2011)
Collections from Lord Howe and Norfolk Islands include three new species and one new locality record of emesine reduviid bugs. From Lord Howe Island Emesopsis cirratus n. sp. the first record of this genus from Lord Howe and Atisne reidi n. sp. are described. Ploiaria weiri n. sp. is described from Norfolk Island. This paper brings the emesine fauna of Lord Howe Island to eight species in six genera and three tribes, and that of Norfolk Island to four species in four genera and three tribes. Our findings support the hypothesis that many invertebrate species are limited in their distributions on these islands, and provide evidence of altitudinal segregation among sisterspecies of the genus Atisne.